Discussion between I. L. Goremykin and S. Yu. Witte on the Zemstvo reform in the western provinces (late 1890s) - Motorova, Nadezhda S. (Journal of the Belarusian State University. History, 2025)
The discussion on the project of the Zemstvo reform in the western provinces of the Russian Empire which unfolded in the late 1890s between the minister of internal affairs I. L. Goremykin and the minister of finance S. Yu. Witte. Official records, their confidential notes, memoirs and diaries are analysed. The prehistory of the development of the project of the Zemstvo reform for the Western region (it was supposed that the system of zemstvo self-government would be implemented in nine provinces, including five Belarusian provinces) is covered, its main provisions are given, the discussion of this draft law with governors and governors-general is characterised. The main attention is paid to the position of I. L. Goremykin as the initiator of the reform and the views of S. Yu. Witte as his opponent. It is noted that during the consideration of the draft law the direction of the discussion changed. I. L. Goremykin considered the introduction of zemstvos in the western provinces as a tool for unifying the all-imperial space and strengthening Russian influence. S. Yu. Witte shifted the emphasis to the problem of the relationship between the zemstvo self-government and the autocracy, consistently defended the need to reform local provincial administration and refuse to establish zemstvos in the Western region. As a result, the draft law developed by the Ministry of Internal Affairs of the Russian Empire was not approved, and I. L. Goremykin was sent into retirement. Discussions on the implementation of the Zemstvo reform in the western provinces continued and led to the establishment of the zemstvo economy departments in 1903 and the formation of the system of zemstvo self-government in 1911. These transformations were realised in three Belarusian (Viciebsk, Minsk and Magiliow) provinces and three Ukrainian (Kyiv, Volyn and Podolia) provinces.